2013
DOI: 10.1111/his.12188
|View full text |Cite
|
Sign up to set email alerts
|

Stromal architecture and periductal decorin are potential prognostic markers for ipsilateral locoregional recurrence in ductal carcinoma in situ of the breast

Abstract: Periductal myxoid stroma and reduced periductal decorin expression seem to be prognostic for overall ipsilateral locoregional recurrence in DCIS, whereas HER2 expression might be a more specific biomarker for invasive recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 43 publications
6
39
0
Order By: Relevance
“…Likewise, myxoid changes in the periductal stroma cannot be overlooked. We previously reported an association between myxoid stromal changes and recurrence rates in DCIS patients . Here, we have determined a robust cut‐off of 33% of ducts surrounded by myxoid changes, and we now aim to further explore the relationship between dichotomised periductal stromal changes and outcome in an independent cohort of DCIS patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, myxoid changes in the periductal stroma cannot be overlooked. We previously reported an association between myxoid stromal changes and recurrence rates in DCIS patients . Here, we have determined a robust cut‐off of 33% of ducts surrounded by myxoid changes, and we now aim to further explore the relationship between dichotomised periductal stromal changes and outcome in an independent cohort of DCIS patients.…”
Section: Discussionmentioning
confidence: 98%
“…The presence and degree of a chronic inflammatory infiltrate in the periductal stroma were recorded semiquantitatively as previously described . Four categories were discerned.…”
Section: Methodsmentioning
confidence: 99%
“…Based on radiological findings, high-density breast stroma has been proposed to be one of the strongest risk factors for invasive breast cancer, second only to deleterious germ line BRCA mutations 51–53. Van Bockstal et al 54 demonstrated that the presence of a predominantly myxoid periductal stroma was the only histopathological feature associated with overall recurrence risk and risk of invasive recurrence, but not with in situ recurrence. Moreover, the same group showed that myxoid stroma-associated DCIS presented significantly more often with reduced expression of periductal decorin, a protein involved in normal collagen fibrillogenesis in breast stroma 54 55.…”
Section: Tumour Cell Extrinsic Factors Involved In Dcis Progressionmentioning
confidence: 99%
“…Van Bockstal et al 54 demonstrated that the presence of a predominantly myxoid periductal stroma was the only histopathological feature associated with overall recurrence risk and risk of invasive recurrence, but not with in situ recurrence. Moreover, the same group showed that myxoid stroma-associated DCIS presented significantly more often with reduced expression of periductal decorin, a protein involved in normal collagen fibrillogenesis in breast stroma 54 55. Remodelling of the stromal ECM appears to be a prerequisite for the progression of DCIS to invasive disease, resulting in the loss of the protective functions normally offered by the cellular and acellular components of the stroma.…”
Section: Tumour Cell Extrinsic Factors Involved In Dcis Progressionmentioning
confidence: 99%
“…The incapacity of MP[fib] to capture cancer cells suggest that fibroblast secrete anti-adhesive proteins that are captured at the surface of the MP. One such anti-adhesive matrix protein is decorin, a small leucinerich proteoglycan, massively synthesized and deposited by fibroblasts in phenotypically normal tissue [40]. Real-time monitoring of colon cancer cell adhesion to a decorin coated substrate revealed significant inhibition of adhesion compared to type I collagen stimulated adhesion [41].…”
Section: Discussionmentioning
confidence: 99%